Development and Evaluation of a Gamified Mobile Application with Two-Dimensional Animation for MPASI Education to Support Stunting Prevention - Diny Anggriani Adnas; Sri Arnilasari; Milasari Milasari (SAINTIS Publishing, 2026)
Inappropriate Makanan Pendamping Air Susu Ibu (MPASI) practices (complementary feeding) remain one of the major contributors to child malnutrition and stunting during the first 1,000 days of life. This study aimed to develop and evaluate a gamified mobile application incorporating two-dimensional (2D) animation as a nutrition education medium to improve mothers' knowledge and adherence to appropriate MPASI practices. A Research and Development (RD) approach using the ADDIE model was employed. The application was developed using the Flutter framework and integrates educational modules, 2D animations, interactive quizzes, local food-based MPASI recipes, daily checklists, and gamification features. Its effectiveness was evaluated using a One-Group Pretest–Posttest design involving 30 mothers. Data were analyzed using descriptive statistics, the Shapiro–Wilk test, the Wilcoxon Signed-Rank Test, effect size analysis, and the USE Questionnaire. The results showed that the mean knowledge score increased from 8.93 to 9.97, while the adherence score improved from 27.53 to 30.53 after using the application. Significant improvements were observed for both variables (p = 0.001), with large effect sizes (r = 0.61 and r = 0.62). The application also achieved an excellent usability score (3.70) and high reliability (Cronbach's Alpha = 0.961). These findings indicate that the proposed application effectively improves mothers' knowledge and adherence regarding MPASI while providing an excellent user experience, demonstrating its potential as a digital nutrition education tool to support stunting prevention.